Associations of Baltic Sea and Mediterranean dietary patterns with bone mineral density in elderly women. Issue 15 (14th August 2017) - Erkkilä, Arja T; Sadeghi, Homa; Isanejad, Masoud; Mursu, Jaakko; Tuppurainen, Marjo; Kröger, Heikki
Abstract: Objective: Dietary quality in relation to bone health has been analysed in relatively few studies. The current study aimed to assess the association of the Baltic Sea diet (BSD) and the Mediterranean diet (MD) with bone mineral density (BMD) among elderly women. Design: Lumbar, femoral and total body BMD were measured by dual-energy X-ray absorptiometry at baseline and year 3. Dietary intake was measured by 3 d food record at baseline. BSD and MD scores were calculated from food and alcohol consumption and nutrient intake. Information on lifestyle, diseases and medications was collected by questionnaires. Longitudinal associations of BSD and MD scores with BMD were analysed using linear mixed models. Setting: Interventional prospective Kuopio Osteoporosis Risk Factor and Fracture Prevention study including women aged 65–71 years and residing in Kuopio province, Finland. Subjects: Women ( n 554) with mean age of 67·9 (sd 1·9) years and mean BMI of 28·8 (sd 4·7) kg/m 2 . Results: Higher BSD scores were associated with higher intakes of fruit and berries, vegetables, fish and low-fat dairy products, and lower intake of sausage. Higher MD scores were associated with higher consumption of fruit and berries and vegetables. BSD and MD scores were associated with higher PUFA:SFA and higher fibre intake. Femoral, lumbar or total body BMD was not significantly different among the quartiles of BSD or MD score. Conclusion: The lack of associations suggest that Baltic Sea and Mediterranean dietary patterns may not adequately reflect dietary factors relevant to bone health.